The Impact of Covid-19 Outbreaks on the Profits of Islamic Banks in Indonesia - Siregar, Sabri Rahman (UI Scholars Hub, 2023)
Abstract The Covid-19 outbreaks hit various business lines in Indonesia. The banking sector has yet to escape the impact of this outbreak. The emergence of the Coci-19 outbreaks in Indonesia can result in the emergence of risks to the performance of Islamic Commercial Banks. This study aims to analyze what factors influenced the level of profitability of Islamic Commercial Banks in the 2020-2022 period when the Covid-19 outbreaks took place in Indonesia. The method used in this research is quantitative by using panel data regression analysis. In this study, there are three categories of variables used. The first category is the banking performance factor with the Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Operating Costs and Operating Income (BOPO). Next is the macroeconomic category with the inflation factor, and finally the monetary category using the BI7DRR factor. This study found that the inflation and BOPO variables had a significant negative effect on the ROA of Islamic Commercial Banks during the observation period. The FDR, NPF, and BI7DRR variables do not affect ROA at Islamic Commercial Banks.